Gambaran Gaya Belajar Mahasiswa Program Studi Ilmu Keperawatan Semester II Angkatan IX Sekolah Tinggi Ilmu Kesehatan Suaka Insan Banjarmasin - Imelda Ingir Ladjar; Munnawaroh RR; Megawati Megawati (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2017)
Backround: Good learning achievement is influenced by many factors, including internal and external factors. One of which is included in the internal factor is the ability of learners to use learning styles effectively. If someone does not recognize learning styles, they will experience barriers to learning and will affect the achievement of the learning purpose. Aim: To know the overview of learning style in undergraduate nursing student of the second semester class IX of STIKES Suaka Insan Banjarmasin. Method: Type of this research was quantitative research with descriptive research design. Population in this research was the students of the second semester of nursing science with 52 nursing students taken by total sampling method. The data was taken by the questionnaire of learning style V-A-K and data analysis was used distribution of frequency. Results and Conclusions: Based on the data analysis, Total 36 (60%) undergraduate nursing student in second semester have visual’s learning style. Then auditory learning style as much as 12 respondents (23%), and kinesthetic learning style as much as 4 respondents (8%). Advice: Teachers and lecturers need to adjust their teaching method while teaching undergraduate nursing student. It will help students to amplify their ability to absorb lesson more effectively.